Fire Safety and Management Awareness - Zafar, Fahmina; Ghosal, Anujit (IntechOpen, 2020)
To ensure a healthy lifestyle, fire safety and protocols are essential. The population boom, economic crunches, and excessive exploitation of nature have enhanced the possibilities of destruction due to an event of a fire. Computational simulations enacting case studies and incorporation of fire safety protocols in daily routines can help in avoiding such mishaps.